Diagnosis and Outcome of Cardiac Paragangliomas: A Retrospective Observational Cohort Study in China - Dong, Xueqi; Meng, Xu; Zhang, Ting; Zhao, Lin; Liu, Fang; Han, Xu; Liu, Yecheng; Zhu, Huadong; Zhou, Xianliang; Miao, Qi; Zhang, Shuyang (Frontiers in Cardiovascular Medicine, 2022)
Background: Cardiac paragangliomas (CPGLs) are rare neuroendocrine tumors that are easily overlooked and difficult to diagnose. Detailed comprehensive data regarding CPGL diagnosis and outcome are lacking. Methods: We retrospectively analyzed a cohort of 27 CPGL patients. This cohort represents the largest such cohort reported to date. Results: The prevalence of trilogy symptoms (concurrent palpitations, hyperhidrosis, and headache) was frequent (9/27, 33.3%). Sensitivity of echocardiography and contrast-enhanced computed tomography for localization of CPGL were 81.8% and 87%, respectively. Octreotide scintigraphy showed 100% sensitivity for detecting GPCLs, while sensitivity of I131-metaiodoben-zylguanidine scintigraphy was only 32.9%. Multiple tumors were found in 29.6% of patients. Most CPGLs originated from the epicardium or root of the great vessels (92.9%) and were mostly supplied by the coronary arteries and their branches (95.7%). Twenty-four patients underwent surgical treatment. Although local invasion was present in 40.0% of patients, it did not affect long-term outcome. Mean follow-up was 6.9 ± 3.6 years. Biochemical remission was achieved in 85% of patients. The recurrence rate was 15%. Conclusions: Manifestations of CPGLs are non-specific and they can be difficult to detect on imaging examinations. Octreotide scintigraphy should be performed in patients with suspected paragangliomas to screen for multiple lesions. Surgical resection of CPGLs can achieve symptom relief and biochemical remission.